Effects of Nopal Mucilage (Opuntia ficus-indica) as Plasticizer in the Fabrication of Laminated and Tubular Films of Extruded Acetylated Starches - Caroline Andreuccetti; Tomás Galicia-García; Fernando Martínez-Bustos; Raimundo Ferreira Grosso; Rubén González-Núñez (International Journal of Polymer Science)
Normal and acetylated rice and waxy maize starches with a blend of nopal mucilage (Opuntia ficus-indica) and glycerol were used for the preparation of laminated and tubular films by extrusion and blown extrusion, respectively. The composition of the formulation was 70% starch (normal or acetylated), 20% glycerol, and 10% nopal mucilage (w/w). The degrees of substitution (DS) for acetylated rice starch (0.94) and waxy maize starch (0.76) present high potential for use as a polymeric matrix in packing materials. The use of nopal mucilage can improve the processability of extruded and tubular films by favoring the increase of some mechanical and functional properties. The films elaborated with nopal mucilage and glycerol present a homogeneous relief without breaking, adhesiveness, and contraction once formed. The elongation values of acetylated waxy maize starch films (33%) were higher than those of rice acetylated films (17%), while the blown films presented a 30% decrease in tensile strength, compared to the laminated films. Acetylation generated more hydrophobic material for the rice starch sample, which can be evidenced by a decreased solubility of the laminated films. Films of both sources of acetylated starch showed a significant decrease in water vapor permeability and showed a plasticized starch disposition-type layer without unmelted starch granules.